2018
DOI: 10.1155/2018/8637812
|View full text |Cite
|
Sign up to set email alerts
|

The Human Skin-Derived Precursors for Regenerative Medicine: Current State, Challenges, and Perspectives

Abstract: Skin-derived precursors (SKPs) are an adult stem cell source with self-renewal and multipotent differentiation. Although rodent SKPs have been discussed in detail in substantial studies, human SKPs (hSKPs) are rarely reported. Understanding the biological properties and possible mechanisms underlying hSKPs has important implications for regenerative medicine particularly clinical applications, as human-derived sources are more suitable for clinical transplantation. The finding that hSKPs derivatives, such as n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…These K19 expressions were distributed throughout the epidermal layer, in the outer root sheath of the hair follicle, and in granulation tissue within the dermis layer. These locations matched those described in previous studies [ 28 , 29 , 31 , 50 , 51 ]. In addition, the intensity of K19 expressions in the SSD group showed a similar pattern as in control group: weak-to-moderate intensity by 7 days post-wounding, a gradual increase to moderate-to-strong intensity by day 14, and a return to moderate-to-weak intensity by 21 days post-wounding.…”
Section: Discussionsupporting
confidence: 89%
“…These K19 expressions were distributed throughout the epidermal layer, in the outer root sheath of the hair follicle, and in granulation tissue within the dermis layer. These locations matched those described in previous studies [ 28 , 29 , 31 , 50 , 51 ]. In addition, the intensity of K19 expressions in the SSD group showed a similar pattern as in control group: weak-to-moderate intensity by 7 days post-wounding, a gradual increase to moderate-to-strong intensity by day 14, and a return to moderate-to-weak intensity by 21 days post-wounding.…”
Section: Discussionsupporting
confidence: 89%
“…Such heterogeneity is a potential risk factor for their clinical transition. Moreover, there are no markers to distinguish purified human SKPs from the rest of the cells originating from hair follicles [ 189 ]. However, by sequential passaging of SKP-derived SCLCs, the purity of the cells could be raised over 95% [ 178 ].…”
Section: Origin and Therapeutic Effects Of Schwann Cell-like Cellsmentioning
confidence: 99%
“…Skin-derived precursors (SKPs) from dermis, firstly described by Toma et al in 2001 (1), are adult stem cells with the capacities of self-renewal and multipotency (2). Conventionally, SKPs are cultured as floating spheres in suspending serum-free medium with required growth factors (3); however, many studies have reported that isolating human SKPs by this protocol has many limitations such as relatively low yield (4), slow growth rate (3), and heterogeneous spheres (5).…”
Section: Introductionmentioning
confidence: 99%